AUTOETHNOGRAPHY AND SPIRITUAL EPISTEMOLOGY IN MUSLIM WOMEN’S LIFE WRITING - Hermawatie, Niela Agustin; Maknun, Lu'luil (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This article explores autoethnography as a form of spiritual epistemology in the study of Islam and gender. Drawing upon feminist hermeneutics and Indonesian Muslim women’s lived experiences, it argues that self-writing is not merely personal expression but a mode of knowing an intellectual and devotional act that integrates reason, emotion, and faith. Using a qualitative reflective framework, the author employs her own journey as a Muslim woman, mother, and doctoral scholar to examine how autoethnography can serve as both method and ibadah ilmiah. The discussion situates this approach within Islamic concepts of tafakkur (contemplation) and muhasabah (self-accounting), connecting them to the works of Amina Wadud, Etin Anwar, and Saba Mahmood. Findings reveal three epistemic dimensions of spiritual self-writing: (1) writing as worship and remembrance, (2) domestic space as an epistemic field of ethical formation, and (3) reflexive authorship as a feminist-spiritual act of reclaiming authority. By merging autoethnography with Islamic historiography, this study proposes an inclusive and embodied mode of scholarship — one that honors lived experience as a source of divine and intellectual illumination.